Animal models of temporal lobe epilepsy following systemic chemoconvulsant administration - Lévesque, Maxime (J Neurosci Methods, 2015)
In order to understand the pathophysiology of temporal lobe epilepsy (TLE), and thus to develop new pharmacological treatments, in vivo animal models that present features similar to those seen in TLE patients have been developed during the last four decades. Some of these models are based on the systemic administration of chemoconvulsants to induce an initial precipitating injury (status epilepticus) that is followed by the appearance of recurrent seizures originating from limbic structures. In this paper we will review two chemically-induced TLE models, namely the kainic acid and pilocarpine models, which have been widely employed in basic epilepsy research. Specifically, we will take into consideration their behavioral, electroencephalographic and neuropathologic features. We will also evaluate the response of these models to anti-epileptic drugs and the impact they might have in developing new treatments for TLE.